Nilai-nilai Akhlak dalam Pembentukan Karakter Menurut Ṣaḥīḥ al-Bukhārī: Moral Values in Character Formation According to Ṣaḥīḥ al-Bukhārī - M. Fadli; Aisyah Kara; Abdul Rahman Sakka (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2025)
This study examines the moral values of character formation as reflected in the Prophet’s hadiths within Ṣaḥīḥ al-Bukhārī. It arises from the contemporary crisis of morality and character, emphasizing the need to revitalize prophetic ethics and spiritual values in Islamic education. The aim of this research is to describe the concept of character formation in the Prophet’s traditions, identify key moral values, and analyze their relevance to modern character education. Employing a qualitative method with a thematic (mawḍū‘ī) approach, primary data were collected from Ṣaḥīḥ al-Bukhārī and supported by secondary literature on hadith interpretation and Islamic education. Data were analyzed descriptively and contextually to uncover the relationship between moral values and practical character education. The findings reveal that the hadiths highlight fundamental virtues such as honesty (ṣidq), trustworthiness (amānah), patience (ḥilm), and humility (tawāḍu‘) as the foundation of a noble Muslim personality. These values establish harmony between the human–God relationship (ḥabl min Allāh) and interpersonal ethics (ḥabl min al-nās). Theoretically, this research enriches thematic hadith studies in the discipline of Islamic education; practically, it contributes to developing a hadith-based framework for moral and character education relevant to the challenges of the modern era.